Evaluating a new concept to integrate compressed air energy storage in spar-type floating offshore wind turbine structures. (15th October 2018) - Sant, Tonio; Buhagiar, Daniel; Farrugia, Robert N.
Abstract: This paper presents a new concept for integrating compressed air energy storage (CAES) into spar-type floating wind turbine platforms. A preliminary investigation of the implications of integrating the proposed concept on the design and dynamic characteristics of a 5 MW floating offshore wind turbine (FOWT) system is presented. A simplified numerical model for sizing the spar to cater for a given compressed air pressure and energy storage capacity is presented. This is then used in a parametric analysis to establish the relationship between the storage capacity, the spar geometry and the additional mass of the floating configuration to support high air pressures. Numerical simulations for the dynamic response are then performed using the marine engineering software tool ANSYS Aqwa © to study the effect of the added steel mass of the spar resulting from CAES integration on the dynamic response characteristics under irregular wave conditions. The results are compared to those derived for a conventional FOWT-spar configuration without an energy storage system. It is shown that it is technically feasible to integrate short-term energy storage capacities on the order of Megawatt-hours. Although integration of CAES in the floating spar results in a significant increase in the weight of the floating structure, it is shown that this also results in a reduction in the motion experienced by the FOWT for the met ocean conditions considered in this study. Highlights: A concept for integrating energy storage in floating wind turbines is evaluated. A simplified model for sizing floating support spars for compressed air is presented. Increased mass of the floating spar results in reduced wind turbine motions.